KLAIM TIDAK LAYAK BAYAR PESERTA JAMINAN KESEHATAN NASIONAL DI LAYANAN RAWAT JALAN RUMAH SAKIT JIWA PROF. DR. SOEROJO, MAGELANG - Vera Otifa; Andreasta Meliala; Yulita Hendrartini (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: The hospital payment mechanism in NationalHealth Insurance era used INA-CBG's package tarif. Theservice payment which had given by hospital was paid byIndonesian National Health Insurance Agency with claimingmechanism. There were several factors and causes thataffected unfeasible payment claim which could harm thehospital.Objective: Identify the factors that caused the unfeasiblepayment claim, identify the cause of the unfeasible paymentclaim, describe the attitude of doctors, the attitude of the leadership of the hospital, the attitude of the administration RSJS,attitude BPJS Health Magelang and describe RSJS leadershipcommunication to the cause of the unfeasible payment claim inthe outpatient service RSJS.Method: This research was an exploratory case study researchwith single holistic case study design. Analysis unit in thisresearch was outpatient services in Prof. dr. Soerojo MagelangMental Health Hospital. Research informants were specializeddoctor and general practitioner RSJS, Prof. dr. SoerojoMagelang Mental Health Hospital's leaders, Prof. dr. SoerojoMagelang Mental Health Hospital's administrators, andIndonesian National Health Insurance Agency branch inMagelang City. The informant selection used purposivesampling. Data collection used in-depth interview anddocument observation. Result: The cause of unfeasiblepayment claim consisted of medical services cause andadministrative cause. The cause of medical services most thatone episode of outpatient, one episode of inpatient anddiagnosis is not emergency. The data difffference between BPJSKesehatan and medical record, non-emergency diagnosis thatconsidered as emergency diagnosis, one episode ofoutpatient/inpatient considered as two episodes ofoutpatient/inpatient. The communication RSJS leaders aboutunfeasible payment claim is not optimal, the attitude doctor'swith less information, the rules have not been clearly linkedspecifificity RSJS in healthcare delivery, indifffference claimservices were they have rendered to the participant JKN,understanding verififier BPJS about medically less in determiningthe unfeasible payment claim into inconsistencies, too tight inthe verifification process and the workload verififier BPJS in RSJSlarge enough can increase in unfeasible payment claim .Theattitude of the leadership of RSJS own conduct follow-up butfollowup information was not communicated to the doctor RSJS,the attitude of the administration RSJS who respond positivelyto minimize the unfeasible payment claim.Conclusion: The leaders' communication, doctor's attitude,Indonesian National Health Insurance Agency's attitude and theunpresented operational standard, and procedure indetermining steps of unfeasible payment claim were factors thatcould enhance the incidence of unfeasible payment claim.